KRISTOLOGI DALAM KITAB IBRANI - Vernando Richardo (Alucio Dei, 2020)
This letter to the Hebrews is addressed to a group of Christians, who, because of constant pressure, may fall away from their belief in Christ. The writer of this letter encouraged them to continue to believe. Three cases were raised by the writer of this letter, namely: First, Jesus is the Son of God - the eternal Son. The Son of God showed His obedience to the Father through His determination to suffer. Second, God has declared Jesus to be an eternal priest who is superior to the priests in the Old Testament. Third, through the intercession of Jesus, those who believe in Him are freed from sin and from fear and death. As the High Priest, Jesus gave humanssalvation that could not be offered by sacrificial ceremonies and other ceremonies in Judaism. The highest value in the book of Hebrews is its teaching about the ministry and priesthood of Christ. In the book of Hebrews there are several characteristics thataccentuate Christ, namely:  The NT book which developed the concept of Jesus' ministry as High Priest. This teaching about Christ is very rich in variety, and uses more than twenty names and titles for Christ